EDUKASI NUMERASI BERBASIS LIVING LAB EKOSISTEM UNTUK KETANGGUHAN EKONOMI DESA BENCANA - Yuni Rhamayanti; Rasmita Adelina; Erin Alawiyah Siregar (JURNAL MathEdu (Mathematic Education Journal), 2026)
Natural disasters cause disruptions to the economic sustainability of rural communities, especially in areas that depend on the agricultural sector and micro enterprises. This condition occurred in Tolang Julu Village, South Tapanuli Regency, which experienced limited economic productivity after the disaster. This study aims to describe the implementation of living lab ecosystem-based numeracy education in supporting the economic resilience of disaster village communities through strengthening productive businesses and numeracy-based economic management. The research uses a qualitative descriptive approach with a participatory design based on the living lab ecosystem. The research subjects consisted of the Harapan Jaya Farmers Group and the PKK Women of Tolang Julu Village who were selected by purposive sampling. Data collection was carried out through observation, semi-structured interviews, documentation, and field notes, then analyzed interactively through data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of numeracy education is able to increase the technical and managerial capacity of the community through hydroponic cultivation, multi-commodity frozen food processing, simple business registration, and digital marketing. The community is starting to be able to apply the calculation of production costs, selling prices, profit estimation, and business management in a more measurable manner. These findings show that living lab ecosystem-based numeracy education has the potential to be an effective community empowerment strategy in strengthening the economic resilience of villages after disasters in a sustainable manner.